Modern electromagnetic sounding systems: situation, trends of development, new ideas and aims - Shuman, V.N. (Geofizicheskiy Zhurnal, 2012)
Stateoftheart and opportunities of development of electromagnetic sounding systems are being considered. The ways and methods of solving old problems as well as new ideas and new aims are under consideration. Key principles of geoelectrodynamics important from the viewpoint of applications are analyzed. In particular, a set of propositions of impedance approach to modern geoelectrics are specified taking into account physical and mathematical aspects of the problem. Necessity of changing “classical” electrodynamic paradigm by a paradigm of fractal electrodynamics of unstable geomedium, which integrates fractal geometry and the theory of electromagnetism is accentuated. It is noticed that application of the theory of fractals, the determined chaos, scale invariance (scaling) and fractional operators open additional possibilities and prospects in processing of observation data and increase of information capacity of sounding systems orienting them to obtaining qualitatively new information on geomedium.